(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, we will explore the role of international organizations in tackling the environmental problems faced by the Aral Sea. We will delve into the causes behind the ecological crisis, examining the consequences of human activities and the ensuing impacts on the environment, economy, and the well-being of local communities. From there, we will assess the efforts made by various international organizations to mitigate these issues and restore the Aral Sea to its former glory.